Do effective audit committees, gender-diverse boards, and corruption controls influence the voluntary disclosures of Asian banks? The moderating role of directors' experience - Muhammad Arsalan Hashmi; Abdullah; Rayenda Khresna Brahmana; Talat Ansari; Muhammad Amin Hasan (Cogent Business & Management, 2022)
The study investigates whether effective audit committees, gender-diverse boards, and corruption controls affect the level of voluntary disclosures of Asian banks. Further, we analyze whether directors' experience moderates the impact of audit committee independence, audit committee meetings, board gender diversity, and corruption controls on voluntary disclosures. We use data for commercial banks operating in six Asian countries, i.e., China, India, Pakistan, Malaysia, Hong Kong, and Singapore. For empirical analysis, we apply several robust statistical techniques. We find that commercial banks with effective audit committees, gender-diverse boards, and corruption controls tend to disclose less information voluntarily as they perceive limited benefits from optional disclosures. Further, we find unique evidence that directors' experience significantly moderates the impact of audit committee independence, audit committee meetings, board gender diversity, and corruption controls on voluntary disclosures of Asian banks. Our unique findings are consistent with the proprietary cost theory. Further, our results indicate that commercial banks operating in countries that maintain rule of law, regulatory quality, and government effectiveness tend to disclose less information voluntarily.
Keywords: 650; Audit committee independence; audit committee meetings; board gender diversity; corruption controls; directors' experience; voluntary disclosures